Hydro-thermal and economic analyses of the air/water two-phase flow in a double tube heat exchanger equipped with wavy strip turbulator. (September 2022) - Zhao, Jinguo; Reda, Shaker A.; Al-Zahrani, Khaled S.; Kumar Singh, Pradeep; Talal Amin, Majdi; Tag-Eldin, Elyased; Emami, Faezeh
Abstract: For the first time in this study, three different heat transfer enhancement methods including bubble injection into the working fluid, wavy strip turbulator (WST) utilization in the inner tube, and the Nanofluid application as the working fluid, were used separately and simultaneously in a double tube heat exchanger (DTHEX). Different air flow rates were injected into the hot fluid. Various turbulators' angles were examined, including 60, 90, 115, and 150°, with water and water-CuO nanofluid as working fluids. The results showed that bubble injection, application of Nanofluid, and the utilization of turbulator increased the heat transfer up to 66%, 74%, and 17%, respectively. Furthermore, the simultaneous use of these three methods increased heat transfer from 33% to 144%. Finally, the most optimal case was chosen utilizing the TEF factor.